On the question of the justification of the principles international legal protection of atmospheric air from pollution - Tussupbekova, S.K.; Taitorina, B.A.; Baisalova, G.Т. (Bulletin of the Karaganda University “Law Series”, 2020)
The article analyzes modern scientific approaches to substantiating the system of principles of international legal protection of atmospheric air from pollution at the present stage of international cooperation of States. The object of the study is the social relations of the planetary scale on the development and implementation of the principles of international legal protection of atmospheric air. The implementation of scientific analysis and generalization is based on an array of normative and scientific material: international legal acts, acts of national law, acts of international organizations, research scientists of the world. The study based on the analysis of international legal acts revealed the specificity of the basic principles of international law. In the context of substantiation of the principles of international environmental law, the role of international intergovernmental conferences, which adopted declarations of principles at the international level, is defined. The results of the scientific debate on the problem of classification of the principles of international legal protection of the environment in General and international legal protection of atmospheric air from pollution in particular are summarized. Based on the analysis of a wide range of sources, it is proved that at the present stage there is no single comprehensive legal framework that determines the legal status of the principles of international environmental law. Many principles lack both clarity and legal consensus on their applicability and are not recognized in legally binding instruments. As a result of the study, conclusions were drawn about the need to adopt a global Covenant on the environment, in which the principles of international environmental law would be systematized.